Contextual Learning Mathematics mediated with Beads to Enhance Elementary School Student Learning Outcomes - Vitiarti . (Pascasarjana Universitas Negeri Malang (UM), 2014)
Pembelajaran Kontekstual Matematika Bermedia Manik-Manik untuk Meningkatkan Hasil Belajar Siswa SD Abstract: The purpose of this research is to improve the learning process and learning outcomes of elementary school students in the addition and reduction of integers through the application of contextual learning mathematics with beads media. The type of research is classroom action research (PTK). This study was conducted in two cycles which each cycle consists of 3 meetings. Based on the results of data analysis and reflection in this study, it shows that the increasing students’ under-standing of concepts of addition and reduction of integers turns higher after obtaining contextual learning of beads media rather than students who received conventional learning. The improved cognitive learning outcomes characterized by the increasing of the percentage in classical complete-ness and the average score of competency test on the second cycle which could exceed the minimum score (KKM). Also, there is a higher tendency of students in doing learning activities after obtaining contextual learning with beads media on the second cycle compared to students who obtain teacher-centered learning.Key Words: learning outcomes, beads media, contextual learning Abstrak: Tujuan penelitian untuk meningkatkan proses pembelajaran dan hasil belajar siswa SD tentang penjumlahan dan pengurangan bilangan bulat melalui penerapan pembelajaran kontekstual matematika bermedia manik-manik. Jenis penelitian adalah penelitian tindakan kelas (PTK). Penelitian dilaksanakan dalam 2 siklus. Setiap siklus terdiri dari 3 kali pertemuan. Hasil analisis data dan refleksi menunjukkan bahwa peningkatkan pemahaman siswa terhadap konsep tentang penjumlahan dan pengurangan bilangan bulat lebih tinggi setelah memperoleh pembelajaran kontekstual bermedia manik-manik daripada dengan pembelajaran konvensional. Peningkatan hasil belajar kognitif ditunjukkan dengan peningkatan persentase ketuntasan klasikal dan skor rata-rata uji kompetensi pada siklus II yang mampu melampaui Kriteria Ketuntasan Minimal (KKM). Peningkatan terhadap aktivitas siswa dalam belajar setelah memperoleh pembelajaran kontekstual bermedia manik-manik lebih tinggi pada siklus II daripada aktivitas siswa pada pratindakan yang memperoleh pembelajaran yang berpusat pada guru (teacher centered).Kata kunci: hasil belajar, media manik-manik, pembelajaran kontekstual